Sustainable industrial design and waste management cradle-to-cradle for sustainable development - Haggar, Salah el-
Sustainable Industrial Design and Waste Management was inspired by the need to have a text that enveloped awareness and solutions to the ongoing issues and concerns of waste generatedfrom industry. The development of science and technology has increased human capacityto extract resources from nature and it is only recently that industries are being held accountable for the detrimental effects the waste they produce has on the environment. Increased governmental research, regulation and corporate accountability are digging up issues pertaining to pollution control and waste treatment and envir.